Perancangan Sistem PPIC di PT XYZ - Cynthia Candradewi; I Gede Agus Widyadana (Jurnal Titra, 2015)
PT XYZ is having difficulty in giving the exact completion time. Sales department always says that the order will be finished in eleven working days. Because the promised processing time always constant, 22.27% of the orders between June 2014 and November 2014 are late. Therefore, the aim of this research is to produce a system for production planning and inventory control, so that the company can estimate completion time accurately. The improvement is the company must estimating completion time before determining processing time in the sales order. Therefore, a detailed production schedule that can be accessed by sales department is needed. Scheduling is created by using the first come first served method, and paying attention to the raw materials availability. The lot size for ordering raw materials is determined by using fixed order quantity method. Production report is created more detail by reporting the actual production daily. The implementation of the improvements can reduce order fulfillment delays, because the processing time in sales order is determined by considering the remaining capacity. The scheduling is made based on the actual condition, therefore can be used to estimate the remaining capacity. The production report can also be used to check whether an order is produced according to the schedule or not.